Evaluasi Penerimaan Mahasiswa Baru Jurusan Tadris Matematika PTKIN-UIN Mataram - Erpin Evendi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to describe the results of evaluation of new student admissions in the 2017/2018 Academic Year PTKIN-UIN Mataram Department using the CIPP model Evaluation method (Context, Input, Process, and Proudact) while the sampling technique used was purposive sampling. The results of interviews, observations, and documentation carried out were analyzed using methods of data reduction, presentation, and conclusion. Based on the results of the study, it was obtained information that the data of students in the mathematics department of the last 3 years showed that the number of non-science students was 35.3%, then the researcher could interpret that there was a 1% decrease in the number of new students who were non-science-based.